Protein-Losing Enteropathy in the Setting of Severe Iron Deficiency Anemia - Jessica Lacy Yasuda MD; Paul A. Rufo MD, MMSc (Journal of Investigative Medicine High Impact Case Reports, 2018)
A 20-month-old boy presented with a 2-week history of pallor and progressive abdominal distention. Nutritional history revealed long-standing excessive cow milk intake. He was subsequently found to be profoundly iron deficient and hypoproteinemic, with an elevated fecal α-1-antitrypsin level and occult blood positive stool, consistent with protein-losing enteropathy. He was treated with cow milk restriction and oral iron supplements, which resulted in resolution of his edema and laboratory anomalies. While small numbers of previous case reports have described the potential association between excessive cow milk intake and severe iron deficiency and protein-losing enteropathy, this constellation of clinical symptoms is infrequently recognized in clinical practice. As iron deficiency is recognized as the most common nutritional deficiency in the United States, it is important to keep excessive cow milk intake in mind when evaluating young children presenting with severe iron deficiency and protein-losing enteropathy.